Coronavirus Disease 2019 Myocarditis: Insights into Pathophysiology and Management - Mahmoud Abdelnabi; Nouran Eshak; Yehia Saleh; Abdallah Almaghraby (European Cardiology Review)
The world is dealing with a global pandemic of severe acute respiratory coronavirus 2 (SARS-CoV-2). Coronavirus disease 2019 (COVID-19), which is the illness caused by SARS-CoV-2, is overwhelming healthcare systems around the world. Although the main clinical manifestations of COVID-19 are respiratory symptoms, several reports have noted myocarditis, cardiomyopathy, arrhythmias and cardiac arrests as COVID-19 complications. Here, the authors highlight the current understanding of the pathophysiology of myocarditis related to COVID-19 and its management.